CFD analysis of the sensitivity of propeller bearing loads to stern appendages and propulsive configurations. (December 2017) - Muscari, Roberto; Dubbioso, Giulio; Ortolani, Fabrizio; Di Mascio, Andrea
Highlights: Effects of stern appendages and the propulsion system on the loads generated by the propeller. Modifications to centreline skeg and direction of rotation of propellers are considered for a twin screw ship. Mitigation of propeller-wake interaction in maneuvring conditions. Abstract: The present investigation focuses on the effects of the stern appendages and the propulsion system on the hydro-loads generated by the propeller during off-design conditions, with particular emphasis on the in-plane components. Recent experimental investigations carried out by free running model tests[7, 8] and CFD analysis[5] for a modern twin screw model, highlighted that maneuvers at small drift angles and yaw rates might be as critical as the tighter ones due to complex propeller-wake interactions. Therefore, design criteria should take into account also these operative conditions, in order to reduce the effects of propeller-wake interaction phenomena that degrade the overall propulsive efficiency, induce shaft/hull structural vibration and increase noise emission. In the present study we analyze the effects of geometric and propulsive modifications with respect to the twin screw configuration studied in[5] . In particular, the effect of the centreline skeg, propeller direction of rotation and control strategies of the propulsion plant on the propeller bearing loads have been investigated from the analysis of the nominal wake in maneuvring conditions, computed by unsteady RANSE simulations coupled with a propeller model based on Blade Element Theory. The considered test cases were turning circle maneuvers with different rudder angles at F N = 0.265.